Immunogenicity and safety of a live attenuated varicella vaccine in healthy subjects aged between 13 to 55 years: a double-blind, randomized, active-controlled phase III clinical trial in China - Yang Zhang; Shiyuan Wang; Guifan Li; Jinhui Shi; Xianyun Chang; Hao Zhang; Fengcai Zhu; Jingxin Li; Hongxing Pan; Jinfang Sun (Expert Review of Vaccines)
Background Adolescents and adults who contract chickenpox are at a higher risk of severe complications. Vaccination with the varicella vaccine (VarV) effectively prevents chickenpox.Research design and methods In this phase III, single-center, randomized, double-blind, active-controlled trial, 1,200 healthy participants were randomly assigned in a 1:1 ratio to receive two doses of either the test vaccine or the active control vaccine. Varicella-zoster virus (VZV) antibody was detected before vaccination and 42 days after the two doses of vaccination.Results The lower limits of the 95% CI for the differences in seroconversion rates and geometric mean titer (GMT) ratios between the two groups were greater than their respective pre-set non-inferiority margins. The overall incidence of Adverse events (AEs) and adverse reactions (ARs) in the test group was significantly lower than those in the control group. Additionally, the incidence rates of swelling and fatigue were lower in the test group compared to the control group after vaccination.Conclusions The test freeze-dried live attenuated VarV demonstrated good immunogenicity and higher safety compared to the active control vaccine in healthy participants aged 13–55 years.Clinical trials registration www.clinicaltrials.gov identifier: NCT06592456.